PERANCANGAN KEMASAN GULO- GULO TAREH NINA PAKAN SENAYAN - Dede Ilham Syarif; dini faisal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
The purpose of this design is to make Gulo-Gulo Tareh Nina's packaging attractive and able to convey information to a new target audience and be able to compete in a wider market. This design uses visual communication design theory, packaging, layout, typography and color. Data collection starts with observation, interview and documentation. Furthermore, the data analysis method used is SWOT (Strength, Weakness, Opportunity, Threat). This design produces the main media packaging in the form of standup pouch. And also equipped by several supporting media such as posters, aprons, stickers, x-banners, t-shirts, tote bags, greeting cards.Keywords: Packaging, Attractive, Target Audience, Competing